The Use of Tarl and Problem-Based Learning to Improve Learning Outcomes and Critical Thinking in Science for 5th Grade - Putri, Putri Rahmawati; Kiki Kartika Widiyanti; Rais Hidayat; Fajar Perdana (Program Studi PGMI, 2025)
This classroom action research aims to enhance students' learning outcomes and critical thinking skills in Natural and Social Sciences by implementing the Teaching at the Right Level approach combined with the problem-based learning model. The background of this study is the low achievement in learning outcomes and suboptimal critical thinking abilities of fifth-grade elementary students in understanding respiratory system concepts. The research was conducted in two cycles using both qualitative and quantitative descriptive methods. Data were collected through observations, assessments of learning outcomes, and critical thinking evaluation sheets. The results indicate that the implementation of differentiated learning strategies and problem-solving significantly enhances students' learning outcomes and critical thinking abilities. The combination of these two approaches has proven effective in creating an active, collaborative learning environment tailored to individual student needs. Therefore, this strategy can serve as a viable alternative for teaching IPAS as well as other subjects in elementary schools.